Why managers matter the perils of the bossless company - Nicolai, Foss. (New York Public Affairs, 2022)
People in the business world are struggling to adapt to a rapidly changing economy. Beset by transformational forces, managers are bombarded with a bewildering array of schemes for how to be a boss and make an organization tick. It's easy to be seduced by futurist fantasies where every company has the culture of a startup, where employees in wacky, whimsical office settings champion the end of old-fashioned corporate hierarchy. Autonomous employees liberated from hierarchies and bosses that oppress people, we are told, are the foundation for breakthrough performance. Be careful what you wish for say Nicolai Foss and Peter Klein. In their important rethinking of the crucial nature of hierarchy and how to be a boss today, they provide the evidence that world-changing issues such as the proliferation of artificial intelligence, economic disruption, empowered knowledge workers, and black swan events such as the pandemic actually make hierarchy and the job of the manager more important than ever. Companies and societies, they show, need authority and hierarchy to coordinate work, including creative work. More surprisingly, Foss and Klein illustrate how the creative use of authority and hierarchy help companies be more agile and flexible. This is not command and control and bossing people around, but the clever use of hierarchy, using the authority of the boss to create highly effective organization where managers focus on creating an environment in which educated, motivated people and teams can thrive"
Keywords: Management